Education and elections: a comparative analysis of party manifestos in OECD countries - Anja P. Jakobi (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2009)
New institutionalism has repeatedly shown that education has become a common institution in current world society, but so far parties have not been the subject of inquiry. This is surprising, given the fact that institutionalization processes relevant to politics should be well observable in political statements. In this article, I compare the political aim to expand educational opportunities in party manifestos of 25 OECD countries. The research question is whether or not there are significant differences in favoring educational expansion over time, across countries and political positions. The article is structured as follows: In a first step, I present the theoretical background of new institutionalism, concluding with three hypotheses related to political parties and educational expansion: We should be able to observe a growing consensus on educational expansion over time; we should able to observe this development across countries; and we should be able to observe such institutionalization in manifestos with different political positions. In a second step, I present data and methods. In the third to fifth steps, I test each of the hypotheses, differentiating the institutionalization of education over time, across countries and across different political wings. The results strongly support the theoretical assumption of new institutionalism. – – Neo-institutionalistische Arbeiten haben wiederholt nachgewiesen, dass Bildung ein wesentlicher Bestandteil einer Weltkultur ist. Während die meisten dieser Analysen vorrangig auf den gesellschaftlichen Wandel auf der Individualebene oder auf die Formulierung nationaler Bildungsgrundsätze fokussierten, untersucht dieses Arbeitspapier mögliche Effekte auf Parteiprogramme. Die grundlegende Annahme ist, dass Institutionalisierungseffekte von Weltkultur spezifischer: die Befürwortung von Bildungsmaßnahmen sich auch in diesen programmatischen Dokumenten nachweisen lassen müssten. Dazu analysiere ich hier quantitativ 25 Länder der OECD-Welt im Hinblick auf Unterschiede über Zeit, über Länder oder zwischen politischen Richtungen. Das Papier ist wie folgt aufgebaut: Zunächst präsentiere ich den theoretischen Hintergrund des Neo-Institutionalismus und leite daraus drei Hypothesen ab, die für Parteiprogramme relevant sind: Es sollte ein zunehmender Konsens hinsichtlich der Befürwortung von Bildungsmaßnahmen sichtbar werden, es sollten dabei keine signifikanten nationalen Unterschiede deutlich werden, und diese Befürwortung sollte in verschiedenen politischen Lagern sichtbar werden. In einem nächsten Abschnitt präsentiere ich die verwendeten Daten das Manifesto-Dataset und die Methoden dieser Untersuchung. In drei weiteren Schritten teste ich dann jeweils die aufgestellten Hypothesen. Die Ergebnisse zeigen, dass in der Tat ein zunehmender Konsens im Hinblick auf Bildung besteht: Das Thema wird über Zeit insgesamt wichtiger, und dies fast ungeachtet der Länder und politischen Richtungen, wenngleich einige Differenzen bestehen bleiben.
Keywords: 370; Bildungspolitik; Parteiprogramm; International; Welt